A review on ash formation during pulverized fuel combustion: State of art and future research needs - Shah, K.; Cieplik, M.; Vuthaluru, Hari (2015)
Solid hydrocarbon fuels-coal and biomass are commonly used for large-scale heat and power generation worldwide. The solid incombustible ash, residing from combustion, leads to several operational issues. Ash-related problems such as slagging, fouling, corrosion, erosion (all resulting in boiler efficiency reduction), emissions of particulate matter and reuse or disposal of captured ashes, may restrict future use of the said fuels. The above mentioned technical bottlenecks are closely related with fuel and combustion process characteristics, as during the combustion process, solid fuel particle undergoes several physical and chemical transformations, which all depend on both the fuel ash chemistry as well as combustion technology. The said transformations include volatilization, fragmentation, chemical reactions, nucleation, coagulation, homogeneous/heterogeneous condensation, All of these processes play a role in the formation of submicron through coarse-sized ash particles are generated. The present paper provides a synthesis of available information on typical fuel characteristics and operating parameters responsible for the said transformations and final size distribution of the ash particles based on critically reported investigations and modeling efforts to date. The fuel characteristics addressed in the review are fuel mineral matter composition and its association (mineralogy), particles' size, shape and density, as well as char structure etc. Also reviewed is the interrelation between the fuel characteristics with operating parameters essential for the understanding of ash transformations. Descriptions of a variety of analytical methods applied to quantify the parameters responsible for ash formation are also covered, including the recognition of modeling efforts to date (from the simple calculations to advance numerical simulations).